Using a Predictor-Corrector Scheme to Compute Navier-Stokes Equations in Three-Dimensional Spherical Coordinates (Journal of Computational Mathematics, 2021)
A new predictor-corrector difference scheme is described for solving the time-dependent Navier-Stokes equations in three-dimensional spherical coordinates. A boundary condition for the pressure is deduced by auxiliary velocity. A multigrid algorithm is employed in solving equations of the pressure. An example of application of this scheme is computed and its results are presented.